2022
DOI: 10.1002/cssc.202200326
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Renewable Thermosets: Kraft Lignin Poly‐adipates

Abstract: Thermosetting polymeric materials have advantageous properties and are therefore used in numerous applications. In this study, it was hypothesized and ultimately shown that thermosets could be derived from comparably sustainable sub‐components. A two‐step procedure to produce a thermoset comprising of Kraft lignin (KL) and the cross‐linker adipic acid (AdA) was developed. The cross‐linking was activated by means of an acetylating agent comprising isopropenyl acetate (IPA) to form a cross‐linking mixture (CLM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Details about the products yields, their molar mass characterization, and other additional information have been reported in our recent paper. [2]'…”
Section: Resultsmentioning
confidence: 99%
“…Details about the products yields, their molar mass characterization, and other additional information have been reported in our recent paper. [2]'…”
Section: Resultsmentioning
confidence: 99%
“…At reflux temperature, the H 2 SO 4 -catalysed reaction of AdA with excess iPAc yielded a cross-linking mixture (CLM) by which lignin was partially esterified to achieve thermoset materials suitable for coatings, with tensile strength in the range of 15-0.33 MPa. 186 Mechanistic studies, carried out by solid-state 13 C MAS NMR and FT-IR, confirmed that both the aliphatic and aromatic hydroxyl groups of lignin were reactive towards the desired transesterification process.…”
Section: Critical Reviewmentioning
confidence: 82%
“…In the second paper, the preparation of a diisopropenyl ester was achieved by the Ru‐catalyzed addition of Z ‐aspartic acid to propyne [49] . Intriguingly, the first investigation on the reactivity of di‐iPEs was carried out by some of us for the fabrication of new polymeric materials derived from lignin [240] . The strategy is described in Figure 3.…”
Section: Diisopropenyl Estersmentioning
confidence: 99%
“…[49] Intriguingly, the first investigation on the reactivity of di-iPEs was carried out by some of us for the fabrication of new polymeric materials derived from lignin. [240] The strategy is described in Figure 3.…”
Section: Diisopropenyl Estersmentioning
confidence: 99%